2017
DOI: 10.1016/j.alcohol.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Persistent negative effects of alcohol drinking on aspects of novelty-directed behavior in male rhesus macaques

Abstract: Humans with histories of prolonged heavy alcohol use exhibit poorer performance on cognitive tasks associated with problem solving, short-term memory, and visuospatial reasoning, even following the cessation of drinking, when compared with healthy controls. It is unclear, however, whether the cognitive problems are a consequence of alcohol exposure or a contributing factor to alcohol-use disorders. Here, we examined the relationship between performance on a novel object recognition (NOR) task and total alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Rhesus macaques have been widely used as a translational model for investigating the neural substrates of human behavior and, particularly, alcohol use and abuse (Grant and Bennett, 2003; Wright and Taffe, 2014; Chandler et al, 2017; Shnitko et al, 2019; Thomas and Czoty, 2019). The present longitudinal study was focused on the measurement of brain changes that occur during late adolescence and early adulthood in rhesus monkeys (3.5–7.5 years of age) because this stage of development confers maximum risk for heavy drinking in humans and macaques (Helms et al, 2014; Substance Abuse and Mental Health Services Administration, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Rhesus macaques have been widely used as a translational model for investigating the neural substrates of human behavior and, particularly, alcohol use and abuse (Grant and Bennett, 2003; Wright and Taffe, 2014; Chandler et al, 2017; Shnitko et al, 2019; Thomas and Czoty, 2019). The present longitudinal study was focused on the measurement of brain changes that occur during late adolescence and early adulthood in rhesus monkeys (3.5–7.5 years of age) because this stage of development confers maximum risk for heavy drinking in humans and macaques (Helms et al, 2014; Substance Abuse and Mental Health Services Administration, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous studies that explored alcohol effects on cognitive flexibility were done with rodents, using a cross‐sectional study design, and demonstrated that EtOH exposure (vapor cambers, intragastric injections) attenuates cognitive flexibility (e.g., Gass et al, ; Sey et al, ). Additionally, in nonhuman primate models of alcohol drinking, chronic alcohol attenuated major executive functions supporting behavioral flexibility, such as working memory, visual discrimination, response time, and accuracy (Chandler et al, ; Crean et al, ; Taffe et al, ; Wright and Taffe, ). In this study, following the chronic alcohol consumption, monkeys, as a group, had nearly identical performance as a control group on the set‐shift task assessed in a sober condition when the testing parameters were the same as before alcohol drinking (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Performance in the novel object recognition task was also associated with alcohol consumption in adult male rhesus macaques (4–6 years old) ( Chandler et al, 2017 ). Monkeys were trained in an operant self-administration protocol the same as above, then allowed an additional month of free access to water and alcohol for 3 h per day.…”
Section: Methods Of Administrationmentioning
confidence: 99%